Globalization and its impact on the development of cultural rights in the Republic of Kazakhstan and the modern world - Birmanova, A.I.; Sopyhanova, A.B.; Lavnichak, A. (Bulletin of the Karaganda University “Law Series”, 2021)
The article considers some issues of human rights development in the world of globalization on the example of human rights in the sphere of culture. For this purpose, the notion of the term “globalisation” and its influence on cultural rights have been identified. The article is devoted to theoretical and methodological analysis of cultural human rights and to the problems of their realization in the modern world under the influence of socio-economic, political, and spiritual modifications. The research is based on a materialistic understanding of the human rights system as a natural result of society's historical development. Dialectical method was used to study doctrinal and legislative sources in the field of cultural human rights as an objective social reality closely connected with social phenomena of political, economic, socio-cultural, and other nature and constantly developing under the influence of various factors in the conditions of globalization. Comparative legal analysis of the norms of constitutions, national laws and international legal acts in recognition and realization of cultural rights allowed to reveal the reform trends in the sphere of their legal regulation in the democratic states of the world. Modern trends of globalization cause changes in the substantive aspect of human rights, which requires a scientific substantiation. As a result of the study, the axiological significance of the realization of cultural human rights was proved; the objective and subjective factors hindering the protection and realization of cultural human rights were revealed.